The Investigation of Incidence and Radiological Findings of Gastrointestinal Stromal Tumor As a Rare Cause of Abdominal Mass (Annals of Medical Research, 2021)
Aim: The aim of the present study was to evaluate the investigation of incidence and radiological findings of gastrointestinal stromal tumors (GIST) as a rare cause of abdominal mass, with current literature review.
Keywords: Gastrointestinal Stromal Tumors; Abdomen; Multislice Computed Tomography; Magnetic Resonance Imaging.